2008
DOI: 10.1104/pp.107.110544
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Naringenin 8-Prenyltransferase, a Flavonoid-Specific Prenyltransferase of Sophora flavescens    

Abstract: Prenylated flavonoids are natural compounds that often represent the active components in various medicinal plants and exhibit beneficial effects on human health. Prenylated flavonoids are hybrid products composed of a flavonoid core mainly attached to either 5-carbon (dimethylallyl) or 10-carbon (geranyl) prenyl groups derived from isoprenoid (terpenoid) metabolism, and the prenyl groups are crucial for their biological activity. Prenylation reactions in vivo are crucial coupling processes of two major metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
143
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 45 publications
4
143
1
Order By: Relevance
“…flavescens Cells-Our previous discovery of SfN8DT-1 indicated that plant prenyltransferases for flavonoids belong to the homogentisate prenyltransferase family involved in vitamin E and plastoquinone biosynthesis (14). Thus, the sequence information of SfN8DT-1 was expected to provide a very powerful tool for isolating cDNAs encoding prenyltransferase that recognized other flavonoids, e.g.…”
Section: Isolation Of Cdnas Homologous To Sfn8dt-1 From Culturedmentioning
confidence: 99%
See 4 more Smart Citations
“…flavescens Cells-Our previous discovery of SfN8DT-1 indicated that plant prenyltransferases for flavonoids belong to the homogentisate prenyltransferase family involved in vitamin E and plastoquinone biosynthesis (14). Thus, the sequence information of SfN8DT-1 was expected to provide a very powerful tool for isolating cDNAs encoding prenyltransferase that recognized other flavonoids, e.g.…”
Section: Isolation Of Cdnas Homologous To Sfn8dt-1 From Culturedmentioning
confidence: 99%
“…A phylogenic tree was made with these candidates and flavonoid prenyltransferases previously reported (SfN8DT-1, SfN8DT-2 isolated from S. flavescens, G4DT from Glycine max) (14,15), in addition to homogentisate prenyltransferases involved in vitamin E and plastoquinone biosynthesis (Fig. 2).…”
Section: Isolation Of Cdnas Homologous To Sfn8dt-1 From Culturedmentioning
confidence: 99%
See 3 more Smart Citations